2010
DOI: 10.1186/1471-2393-10-31
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of a community-based intervention promoting multiple maternal and neonatal care practices in rural Nepal

Abstract: BackgroundThe challenge of delivering multiple, complex messages to promote maternal and newborn health in the terai region of Nepal was addressed through training Female Community Health Volunteers (FCHVs) to counsel pregnant women and their families using a flipchart and a pictorial booklet that was distributed to clients. The booklet consists of illustrated messages presented on postcard-sized laminated cards that are joined by a ring. Pregnant women were encouraged to discuss booklet content with their fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 21 publications
(17 reference statements)
1
40
0
Order By: Relevance
“…The involvement of FCHVs in community health interventions in Nepal has effectively improved population-based coverage for various health services [17][18][19][20][21]. A post disaster health promotion intervention study involving FCHVs in an earthquake affected district in Nepal showed that their involvement helped in improving the facility delivery among the mothers from 63 to 83% [21].…”
Section: Role Of Fchv In Community Linkagementioning
confidence: 99%
“…The involvement of FCHVs in community health interventions in Nepal has effectively improved population-based coverage for various health services [17][18][19][20][21]. A post disaster health promotion intervention study involving FCHVs in an earthquake affected district in Nepal showed that their involvement helped in improving the facility delivery among the mothers from 63 to 83% [21].…”
Section: Role Of Fchv In Community Linkagementioning
confidence: 99%
“…The HARDIC trial was designed using a peer education approach, which has earlier proved efficient in improving dietary knowledge and behavior and promoting better maternal and neonatal care practices in rural areas of Nepal and other countries [14,39,40]. Because the use of behavior theories during the development of a health promotion program improves the likelihood of positive behavior changes [41], the HARDIC intervention was based on health behavior theories that target both individuals (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Process evaluations have been used to evaluate the implementation of other community-based interventions, including within maternal and newborn health (Dynes et al, 2011;McPherson et al, 2010;Rath et al, 2010). However, there is still a notable gap in the literature around complex behavior change interventions like EQUIP, with many interventions reporting only on impact and not on process (Butterfoss, 2006;Michie, Fixsen, Grimshaw, & Eccles, 2009;Workgroup for Intervention Development and Evaluation Research, 2009).…”
Section: Discussionmentioning
confidence: 99%